Bioactivity of Piper extracts on Tuta absoluta (Lepidoptera: Gelechiidae) in tomato - Brito, Elaine Ferrari de; Lopes Baldin, Edson Luiz; Macedo Silva, Roney de Carvalho; Ribeiro, Leandro do Prado; Vendramim, José Djair (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the bioactivity of ethanolic leaf extracts from four species of the genus Piper against the tomato leafminer Tuta absoluta (Lepidoptera: Gelechiidae) under laboratory conditions. The evaluated species were: P. amalago var. medium, P. glabratum, P. mikanianum, and P. mollicomum. In the initial screening assay (extract concentration of 2,000 mg L‑1), all tested extracts caused significant larval mortality, particularly the extract of P. amalago var. medium; however, no extracts reduced the weight of the surviving larvae. The extract from P. amalago var. medium at the concentration of 1,011 mg L‑1 caused a significant lengthening of the larval and pupal stages. The ethanolic leaf extract of P. amalago var. medium is promising for the control of T. absoluta larvae in tomato, since it exhibits acute toxicity toward these caterpillars at the concentration of 2,000 mg L‑1 and affects the insect’s development by reducing its survival and lengthening the larval and pupal stages.